Representação mental da língua e da cultura norte-americanas: uma análise crítica do discurso de professores brasileiros de língua inglesa. - Assis, Claudete Santana (2020)
The current work aimed at analyzing the speech of nine Brazilian teachers who teach English as a Foreign Language at three renowned institutions of English language teaching in the city of Recife, Pernambuco, in order to verify if the mental models built justify the polarization of the groups denominated as groups of US and THEM (VAN DIJK, 2015a). That polarization has occurred in a reverse way since Brazilian teachers look up the American culture to the detriment of theirs. It is known that the mental models are formed on the basis of entertainment media (television, songs, cinema to name but a few), food and electronics products among others and even by personal experiences. This polarization reversal was caused in Brazil, not only by the exposure of these products, but also by the country's historical context. The insertion of the American government in Brazil and its hegemonic power began, effectively, around the 1940s when they established a Bureau in Brazil with the purpose of cultural exchange. Nonetheless, it was nothing more than the implantation of the American hegemony which happened between diplomatic agreements with Brazil and that were instituted by American institutions, along with the export of its English language. The research uses a qualitative, transversal and analytical methodology, according to Bortolozzi and Bertoncello (2012) and Rodrigues (2007) and had its analyzes guided in the light of Critical Discourse Studies, having Van Dijk as the main theoretician so that we can comprehend the sociocognitive discourse aspects and their components using the discourse triangle proposed by the author, discourse-cognition-society, as well as Souza (2018), Moita Lopes (1996) and Rajagopalan (2008) among others to understand the historical context of the North American culture coming to Brazil and the mental representations built subjectively.